Work Engagement as a Mediator between Perceived Organizational Support and Job Satisfaction among Local Government Employees in Indonesia - Alhutari Restu Illahi; Nia Ariyani Erlin (Al-Qalam Institue, 2026)
This study aims to examine the effect of perceived organizational support on job satisfaction and to analyze the mediating role of work engagement among employees of the Community and Village Empowerment Office (DPMD) of Padang Pariaman Regency, Indonesia. This research employed a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to all 36 employees using a census sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3, including measurement model assessment, structural model evaluation, and mediation analysis. The results indicate that perceived organizational support has a positive and significant effect on job satisfaction (β = 0.480, p = 0.002) and work engagement (β = 0.809, p < 0.001). Furthermore, work engagement positively influences job satisfaction (β = 0.362, p = 0.030) and significantly mediates the relationship between perceived organizational support and job satisfaction (β = 0.293, p = 0.047). The study concludes that organizational support enhances employee satisfaction by strengthening psychological engagement. The findings imply that public sector organizations should prioritize supportive leadership, employee recognition, and engagement strategies to improve employee well-being and organizational effectiveness.